Piękno jako szczyt natury oraz kultury – filozoficzno-teologiczne ujęcie piękna - Grzegorz Sobczak (Wrocławski Przegląd Teologiczny)
The beauty revealed oneself in two spheres of the one reality: in nature and in culture – but as trancendentalium, beauty as exceeding beyond this reality. This way temporary beauty which is present in nature and culture is leading to Absolute Beauty. Article is presenting specifity of the beauty for nature and culture. So article is presenting the natural, craft and artistic dimension of the beauty in nature and culture, which entails philosophical dimension whom identifying beauty with being and theological dimension which suiting Divine element for the Beauty.